Ultrasound-assisted extraction optimization of polyphenols from Boletus bicolor and evaluation of its antioxidant activity - Hu, Dong-Bao; Xue, Rui; Zhuang, Xiao-Cui; Zhang, Xin-Sha; Shi, Sheng-Li (Frontiers in Nutrition, 2023)
Natural antioxidants are widely used as dietary supplements or food additives. To assay the activity of natural antioxidant substances in Boletus bicolor, an optimized method of ultrasound-assisted extraction (UAE) was proposed for the effective extraction of polyphenols from the mushroom Boletus bicolor and evaluated by response surface methodology (RSM). In this study, ethanol concentration, ratio of solvent to solid, ultrasonic time and temperature were investigated and optimized using a central composite rotatable design. The optimal extraction conditions were as follows: ethanol concentration, 42%; ratio of solvent to solid, 34:1 mL/g; ultrasonic time, 41 min; and temperature, 40℃. Under these conditions, the optimized experimental polyphenol value was (13.69±0.13) mg/g, which was in accordance with the predicted value (13.72 mg/g). Besides, traditional extracting methods, including maceration and soxhlet extraction methods, were also carried out for comparison. In addition, the antioxidants activities of mushroom extracts obtained by UAE exhibited good 2,2-dipheny-1-picrylhydrazyl radical(DPPH•), 2,2-azino-bis(3-ethylbenzothiaziline-6-sulfonic acid) radical(ABTS+•), hydroxyl radical (OH•) , nitric radical (NO2-) scavenging activities, and ferrous ion (Fe2+) chelating capacity, with IC50 values of 98.17, 49.80, 60.79, 174.46, 123.00 μg/mL, respectively. Finally, eight phenolic compounds in the extract were identified and quantified by UPLC-MS, which were syringic acid, chlorogenic acid, gallic acid, rosmarinic acid, protocatechuic acid, catechin hydrate, caffeic acid and quercetin dihydrate. The density function theory calculations showed that chlorogenic acid presented the highest HOMO energy (-0.02744 eV) and the lowest energy difference (-0.23450 eV) among the studied compounds, while the lowest HOMO energy and the highest energy difference is found for quercetin dihydrate. Thus, chlorogenic acid and quercetin dihydrate are expected to possess the strongest and the weakest electron-donating ability in eight main polyphenolic compounds of Boletus bicolor, accordingly. The results showed that the UAE technique developed in this work was an efficient, rapid, and simple approach for the extraction of polyphenols with antioxidant activity from Boletus bicolor. This study is helpful for utilization of the delicious mushroom.